The role of 7-hydroxymatairezinol in modulation of estrogen metabolism and therapy for mastopathy - Anna N. Rubashkina; Nina P. Lapochkina; Ivan Yu. Torshin; Olga A. Gromova (IP Berlin A.V., 2020)
Quantitative estimates of the effect of 7-hydroxymatairesinol (7-HMR) intake on estrogen balance and clinical aspects of the course of fibrocystic mastopathy have been carried out. Aim. Assessment of effects 7-HMR on metabolism of estrogen (16a-OHE1, 2-OHE2, 2-OHE1, 2-OMEE1, 4-OMEE2, 4-OHE1, a ratio 2-OHE1/16a-OHE1, 2-OHE1/2-OMeE1 and 4-OHE1/4-OMeE1) and progesterone in daily urine at patients with fibrous and cystous mastopathy in the post-menopausal period. Materials and methods. The analysis of metabolites of estrogen (16a-OHE1, 2-OHE2, 2-OHE1, 2-OMEE1, 4-OMEE2, 4-OHE1, ratios 2-OHE1/16a-OHE1, 2-OHE1/2-OMeE1 and 4-OHE1/4-OMeE1) and progesterone in daily urine with use of solid-phase immunofermental set (IFA) of Amerscham International on the analyzer of Amerkard by means of standard sets is carried out. Statistical 10.0 and Microsoft Excel spreadsheets were used in statistical material processing. Results. It was found that taking 7-HMR (60 mg/day, 1 month) contributes to normalizing estrogen metabolism (decreasing estradiol, estrone, estriol, 16a-OHE1) and improves the clinical symptoms of mastopathy. Conclusions. In patients with FCM, 7-HMR contributes to a decrease in hyperestrogenia-related tumor risks by lowering estrogen metabolites levels.